The one health paradigm: a review - Nagarajan, Lydia Thenmozhi; Mohammed, Imran Pasha; Shenoy, Rekha P.; Junaid; Amanna, Supriya; Apoorva; Prabhakar, Pramada; Nasar, Hifsu (International Journal Of Community Medicine And Public Health, 2025)
The One Health paradigm aims to achieve optimal health outcomes by recognizing the interconnection between people, animals, plants, and their shared environment. The increasing emergence of zoonotic diseases, environmental disruptions, and antimicrobial resistance (AMR) calls for an integrated and transdisciplinary approach. This review explores the origin and evolution of the One Health concept, its core principles, its alignment with primary health care strategies, and its role in combating zoonotic diseases and AMR. Special attention is given to the Indian context, highlighting significant national initiatives that illustrate the implementation of One Health. By analyzing current frameworks, we also emphasize the necessity of intersectoral collaboration, policy integration, and sustainable practices. The review concludes with recommendations for future directions, including global surveillance, community participation, and capacity building. Overall, the One Health approach presents a comprehensive strategy to confront global health challenges through unified efforts in human, animal, and environmental health sectors.